Effects of the nematicide imicyafos on soil nematode community structure and damage to radish caused by Pratylenchus penetrans - Wada, Satoko (Journal of nematology, 2011)
The effects of the non-fumigant nematicide imicyafos on soil nematode community structure and damage to radish caused by Pratylenchus penetrans were evaluated in two field experiments in consecutive years (2007 and 2008). Nematode densities in soil at 0 - 10 cm (the depth of nematicide incorporation) and 10 - 30 cm were measured. The application of imicyafos had a significant impact on the density of P. penetrans at 0 - 10 cm but had no effect on free-living nematode density. PCR-DGGE analysis conducted using extracted nematodes showed that the nematode community structure 12 d after application in 2007 was altered by the application of imicyafos at the 0 - 10 cm depth, but not at 10 - 30 cm. No significant differences were observed in the diversity of the nematode community at harvest (89 and 91 d after application) between the control and imicyafos treatments in both depths and both years. In both years, the damage to radish caused by P. penetrans was markedly suppressed by the nematicide. Overall, the nematicide imicyafos decreased populations of P. penetrans in soil and thereby decreased damage to radish, while having little impact on the soil nematode community